Impact of Music Intervention (Listening to Indian Classical Music) on Mental Wellbeing during COVID-19 Pandemic - Roan Mukherjee (Jurnal Litbang Edusaintech, 2021)
Background: Reports show that mental wellbeing may be negatively affected by the COVID-19 pandemic. The ragas of Indian classical music are believed to have therapeutic effects. This study was done to investigate the impact of an Indian raga on mental wellbeing during the COVID-19 pandemic. Materials and Methods: It was a one-group before-after design study. A total of 45 adult subjects of Kolkata, recruited online, using convenience sampling during the lockdown, underwent a pre-test via Google forms using Warwick-Edinburg Mental Wellbeing Scale (WEMWBS) to evaluate mental wellbeing before the administration of music intervention. After two weeks of music intervention, that consisted of passively listening to raga Hamsadhwani, a post-test using the same scale and the same medium was done. Results: The results showed that the post-test mean of the total score 51.1 (SD = 3.9) of WEMWBS was significantly (p< 0.001) higher than the pre-test mean of the total score 30.9 (SD = 4.6). The same trend was reflected by the mean difference pertaining to all of the components of WEMWBS. Conclusion: It was concluded that raga Hamsadhwani may be effective in improving mental wellbeing in a pandemic situation. There is a need to do more work by improvising the research design employed in the present study. This will help to interpret more accurately and more meaningfully the effects of Indian raga music on mental wellbeing.